On the occasion of the eighty-fifth anniversary of France Novak - Merše, Majda (Slavia Centralis, 2021)
The article is dedicated to the expert on Slovene language, linguist, lexicographer, and in recent years mainly researcher of the history of the Slovene language France Novak.
Keywords: France Novak; eighty-five years old; lexicography; Slovene studies; history of the Slovene language; jubilee